Reformulating Indonesia’s Minimum Wage Policy: Transitioning from a Minimum Wage-Based Approach to a Productivity-Based Wage Structure - Nandariztyani, Dityas; Adi, Isbandi Rukminto (The Sunan Ampel Review of Political and Social Sciences, 2025)
This study examines the reformulation of Indonesia’s minimum wage policy under Government Regulation (GR) No. 51 of 2023, which was introduced following Constitutional Court decisions that mandated revisions to the Job Creation Law. The policy reform aims to balance worker protection, business certainty, and economic equity within the broader framework of social welfare. Using a qualitative research approach, data were collected through in-depth interviews with government officials, labor unions, employer associations, and members of the National Wage Council, complemented by document analysis of regulatory texts and consultation records. The findings reveal that the reformulation was driven by four structural issues: mistargeted application of the minimum wage, industrial burden, recurring labor conflicts, and weak implementation of wage structure and scale. The formulation process combined rational, political, and incremental decision-making models, reflecting bounded political rationality. Empirical results indicate that the policy’s implementation has led to informal compromises between employers and workers, weak enforcement mechanisms, and persistent wage inequality. Although the regulation introduces a shift toward a productivity-driven wage system, its effectiveness remains limited by institutional and administrative constraints. The study concludes that aligning policy intentions with social welfare values requires strengthening institutional enforcement, expanding the application of structured wage systems, and promoting inclusive social dialogue to ensure that the minimum wage functions effectively as both a social safety net and an economic stabilizer in Indonesia’s evolving labor market.